a=x+4,b=9-x,c=x. if 2a -b-3c = ?
Attachments:
![](https://hi-static.z-dn.net/files/de1/f39ef1bf44bd1114d8d0c68454f1b786.jpg)
Answers
Answered by
3
a= x+4, b=9-x, c=x
2×(x+4)-(9-x)-3×(x)
= 2x+8 -9+x-3x
= 2x -1 -x
= x - 1. answer
Hope you had got it....
2×(x+4)-(9-x)-3×(x)
= 2x+8 -9+x-3x
= 2x -1 -x
= x - 1. answer
Hope you had got it....
Laxman4141:
hi
Answered by
2
2a-b-3c
a=x+4,b=9-x,c=x
2(x+4)-(9-x)-3(x)
2x+8-9+x-3x
2x-2x-1
x-1
a=x+4,b=9-x,c=x
2(x+4)-(9-x)-3(x)
2x+8-9+x-3x
2x-2x-1
x-1
Similar questions
Chemistry,
9 months ago
Math,
1 year ago
Physics,
1 year ago
Computer Science,
1 year ago
Math,
1 year ago